Pedagogical Content Knowledge in Mathematics of Future Elementary School Teachers Who Are About to Start Their Mathematics Education Courses - Samková, Libuše (Scientia in educatione, 2016)
The study focuses on investigating pedagogical content knowledge in mathematics in the context of future elementary school teachers’ education. The primary strategy explored in this study is the use of a teaching tool called “concept cartoons”. The ﬁrst part of the contribution gives an overview of the relevant research, while the second part describes our own empirical research and a preparatory study. The preparatory study focused on the ways in which concept cartoons could be used as a tool for investigating pedagogical content knowledge. The research itself focused on the investigation of pedagogical content knowledge of future primary elementary school teachers. The participants of our research were students of the second year of a ﬁve-year master degree university programme for future elementary school teachers who had not yet attended the respective mathematics education college course. We focused on assessing their knowledge in the ﬁeld of number systems. The results of the research have conﬁrmed that some future teachers are able to acquire some expertise in pedagogical content knowledge in non-formal settings, during their attendance of K-12or non-didactic university courses. The data analysis revealed the several participants had good knowledge of the relevant tasks and pupils’ misconceptions. Some participants, however, were unable to distinguish between the act of identifying a mistake and the ability to identify the cause and potential remedy of a mistake. They also had unrealistic expectations about pupils’ levels of reasoning. General results of the research are demonstrated by sample data segments.